Using GIS in designing and structuring a spatial data base for soil in Tukara, Libya - Elkhboli, M. M. H. (Al-Mukhtar Journal of Sciences, 2007)
This study show the possibility of using the GIS technology to connect information, which is very important especially with varied data. This system is also useful for planning studies. A spatial data base was designed and prepared for soil properties by saving digital and text data using ArcView GIS 3.2 and its software through consecutive steps. The results were connected with its spatial (geographical) sites in the area of study. Different analytical processes were carried out, resulting in the producing of maps for some soil properties such as soil depth, soil texture, calcium carbonate content and the mineral nutrient elements, which may have an effect on agricultural productivity.